Socially Responsible Public Procurement and the Social Economy: European and Global Institutional Approaches - Lamprinidis, Lampros (Journal of Public Policy and Administration, 2025)
Purpose: This paper examines Socially Responsible Public Procurement (SRPP) as a strategic institutional tool for advancing the Social Economy at both European and global levels. It investigates the alignment of SRPP with inclusive, sustainable development goals, focusing on key initiatives such as the EU Social Economy Action Plan, the 2023 Council Recommendation, and the UN General Assembly Resolution 77/281. Methodology: The research adopts a comparative policy analysis framework, assessing legislative instruments, international resolutions, and governance models. It incorporates multi-level governance and evaluates the practical impact of SRPP on Social Economy Entities (SEEs), complemented by a review of global and EU-level policy milestones. Findings: SRPP is revealed as a transformative procurement approach that embeds social objectives into public spending. When effectively implemented, it facilitates the growth of SEEs, promotes local resilience, and fosters inclusive labor markets. However, mainstream adoption is hindered by institutional fragmentation, limited awareness, and inconsistent application across Member States. Unique Contribution to Theory, Practice, and Policy: The study offers concrete policy recommendations, emphasizing the need for a supportive legal and fiscal ecosystem, improved stakeholder capacity-building, and transnational cooperation. It positions SRPP as a pivotal driver for advancing the Proximity Economy and the broader social and solidarity-based economic models.